Three phase corrosion of pipeline steel: Size effects of deposited solids under water droplets and an oil diffusion barrier - Hongxing Liang; Rebecca Filardo Schaller; Edouard Asselin (Journal of Pipeline Science and Engineering, 2021)
Existing studies have examined either under deposit corrosion in bulk solutions or underoil droplet corrosion without deposits. Yet, neither of these scenarios represents the conditions existing within a diluted bitumen pipeline where underoil droplet corrosion occurs in tandem with under deposit corrosion. Herein, this industrially important 3-phase system – solid deposit, aqueous droplet, oil cover – is studied for the first time. In particular, the relationship between varying deposit particle size and underoil droplet corrosion is established. Scanning electron microscopy coupled with profilometry was used to monitor droplet corrosion over time for API-X100 pipeline steel covered with different sized silica particles underneath simulated diluted bitumen. A zero resistance ammeter was used to validate the observed corrosion from the immersion experiments. The data indicate that localized corrosion coupled with uniform corrosion occurred beneath the large (80% of the cumulative particle size distribution less than 540 µm) and small (80% of the cumulative particle size distribution less than 43 µm) silica covered underoil droplets on API-X100 pipeline steels after 24 h of exposure. The underoil droplet corrosion of silica covered steel has maximum localized penetration predominantly around the silica pile perimeter. With continued exposure, up to 240 h, the corrosion beneath the two sizes of silica continues to develop with a difference in rate. The maximum penetration rate (13.58±0.76 mm/year) of localized corrosion under the large silica particles was higher than that (10.02±0.87 mm/year) of the localized corrosion beneath the small silica particles.